On the Stability of an Islamic Financial System - Askari, Hossein; Krichene, Noureddine; Mirakhor, Abbas (PSL Quarterly Review, 2014)
In an Islamic economy, the financial sector functions to support the real sector. There are no interest rate based debt instruments. Financial assets are based on risk and return sharing and are contingent claims. Real as well as monetary forces determine the rate of return. As in traditional general equilibrium theory, there is a price system comprised of a real rate of return to capital and a price level of commodities that simultaneously clears asset and commodity markets. An Islamic financial system is shown to be stable, namely the economy evolves from short-term equilibrium to a stable long-term equilibrium. Key Words: Islamic Finance, Financial Stability, Equilibrium, Chicago Plan JEL codes: E2, E3, E4, and F4.